2015
DOI: 10.1186/s40360-015-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune- and miRNA-response to recombinant interferon beta-1a: a biomarker evaluation study to guide the development of novel type I interferon- based therapies

Abstract: BackgroundThe innate immune receptor RIG-I detects viral RNA within the cytosol of infected cells. Activation of RIG-I leads to the induction of antiviral cytokines, in particular type I interferon, the inhibition of a T(H)17 response as well as to the suppression of tumor growth. Therefore, RIG-I is a promising drug target for the treatment of cancer as well as multiple sclerosis. A specific ligand for RIG-I is currently in preclinical testing. The first-in-human trial will need to be carefully designed to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In a large international cohort study of MS, after exclusion of patients with a previous history of depression, no association between IFN-beta treatment and induction or exacerbation of depressive symptoms was observed (Schippling et al., 2016). However, in the present study, the occurrence of psychopathological symptoms was observed even if participants with a history of depression or depressive symptoms (as assessed by the psychiatric disease diagnostic manual, MINI) were excluded by the admission criteria (Coenen et al., 2015).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In a large international cohort study of MS, after exclusion of patients with a previous history of depression, no association between IFN-beta treatment and induction or exacerbation of depressive symptoms was observed (Schippling et al., 2016). However, in the present study, the occurrence of psychopathological symptoms was observed even if participants with a history of depression or depressive symptoms (as assessed by the psychiatric disease diagnostic manual, MINI) were excluded by the admission criteria (Coenen et al., 2015).…”
Section: Discussionmentioning
confidence: 68%
“…Functional MRI measurements were undertaken as part of the “Immune- and miRNA-response to recombinant IFN-beta in healthy volunteers and patients with relapsing remitting multiple sclerosis” clinical study (trial short title: RESI), listed under EudraCT-number “2012-005475-13” in the EU Clinical Trials Register database (Coenen et al., 2015). The clinical study was conducted at the phase I Unit and the Clinical Study Core Unit of the University Hospital Bonn in accordance with the ICH Guideline for Good Clinical Practice, the relevant national regulations and the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And it may be the main cause of the downregulation of IFN‐I in the MS patients. An investigation approved the benefits of RIG‐1 ligand in activating the RIG‐1 pathway and the improvement of clinical presentation of MS [19]. Accordingly, it has been shown that using RIG‐1 ligands leads to decreased Th1 and Th17 T‐cell responses within the CNS [20].…”
Section: Discussionmentioning
confidence: 99%
“…The first longitudinal study on the miRNA expression changes in response to IFN-β showed that an up-regulation of IFN-β-responsive genes was coupled to a down-regulation of several miRNAs (including members of the miR-29 family) in peripheral blood mononuclear cells (PBMCs) of RRMS patients [78]. The involvement of miRNAs in response to IFN-β was pointed out by a clinical trial, where the participants received standard IFN-β therapy for nine days [79]. Data showed that aberrant expression levels of miR-145 and miR-20a-5p were normalized in the whole blood of RRMS patients treated with IFN-β [80].…”
Section: Multiple Sclerosismentioning
confidence: 99%